Synthesis of triazole-containing ciprofloxacin conjugate and its in silico test as a cytochrome P450 ligand - Faletrov, Yaroslav V.; Glinskaya, Liliya I.; Horetski, Matvey S.; Panada, Jan V.; Frolova, Nina S.; Shkumatov, Vladimir M. (Journal of the Belarusian State University. Chemistry, 2021)
Cytochromes P450 are hem-containing monooxygenases which catalyse biosynthesis of many compounds playing an essential role in cellular functions as well as degradation of drugs and xenobiotics. Some P450s (e. g., human CYP19 and CYP17, fungal CYP51) are valid target proteins for some drugs. The others P450s are also interesting for pharmacology-related researches. Aiming to design new fluorescent inhibitor of P450s we have synthesised the azole-bearing conjugate of ciprofloxacin (CPF-bab-Z1). To estimate potential of the compound as a ligand for CYPs we performed high-throughput virtual screening (multiple docking calculations) for CPF-bab-Z1 and multiple known 3D structures of P450s. The best affinity for CPF-bab-Z1 (the smallest value of energy of binding is equal -12.5 kcal/mol) were found for protein with PDB code 5esh among 28 structures of CYP51. The calculated pose of CPF-bab-Z1 in the active site of the protein is characterised by cyclopropyl (but not azole) proximity to the heme iron of the CYP51. The data obtained demonstrate perspectives for in vitro investigations of CPF-bab-Z1 with P450s.
Keywords: P450; fluorescence; azoles; inhibitors; docking; ciprofioxacin